Establishment of multiplex PCR for the detection of common neurotropic viruses. - Gopalakrishnan, V. (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Viral infections of the central nervous system (CNS) may result in clinical syndromes like aseptic meningitis, encephalitis and myelitis. These infections are often difficult to diagnose using conventional laboratory techniques like viral culture and serology. These methods are also time consuming and unsatisfactory. Hence a study was designed to develop a rapid technique to detect the viral etiology. In this study a reverse transcriptase (RT) multiplex PCR to detect viral etiologies in CNS infections was standardized. The RT multiplex PCR was designed to detect enterovirus, herpes simplex and varicella zoster viruses. Three sets of primers were employed for their detection. Amplification of target sequences was qualitatively analyzed by looking for the presence or absence of amplicons on a 2o/o agarose gel stained with ethidium bromide. Sensitivity of the PCR has been ascertained. Further, 3 sets of primers were used to perform a second PCR (nested), which confirms the product specificity, and also helps in increasing the sensitivity of the assay. The RT multiplex PCR standardized can be employed to detect herpes, varicella and enteroviral infections.